Chronic orchalgia after surgical exploration for acute scrotal pain in children. Issue 3 (June 2016) - Hart, Jodi; Pastore, Gianna; Jones, Matthew; Barker, Andrew; Khosa, Japinder; Samnakay, Naeem
Summary: Objectives: The aim was to review the pediatric cohort undergoing surgical exploration for acute scrotal pain at our institution and assess the entity of chronic orchalgia post exploration in this cohort. Materials and methods: A retrospective review of all pediatric patients who underwent surgery for acute scrotal pain at a single institution between 1 January 2001 and 1 January 2012 was conducted. Results: A total of 1084 patients underwent scrotal exploration for acute scrotal pain where the underlying cause could not be clinically ascertained. Causes found at exploratory surgery are shown in the table. Forty-four children (4.1%) re-presented with another episode of acute scrotal pain and underwent re-exploration. A hundred of the 772 children with testicular appendage torsion at initial exploration had unilateral exploration only. Seven (7%) of these re-presented with contralateral appendage torsion. The complication rate of initial scrotal exploration was 5.6% and that of re-exploration was 6.8%. All complications were managed conservatively except for a painful reactive hydrocele that underwent the Jaboulay procedure. Fifteen (1.4%) children in this cohort developed chronic orchalgia. Thirteen (87%) of these had definite pathology found at initial exploration. One of 61 (2%) with postoperative complications (a reactive hydrocele) developed chronic orchalgia. Pediatric chronic pain specialists were consulted for all patients. In 10 of the 15 (67%), significant comorbidities included constipation, anxiety, somatization, hydrocele, dysfunctional voiding, and multiple joint pain. The Jaboulay procedure for reactive hydrocele and re-exploration to pex the testes due to suspected intermittent testicular torsion resolved chronic orchalgia in one patient each. Discussion: Pediatric chronic orchalgia post exploration is uncommon. It has a multifactorial etiology. Comorbidities are common. It is possible that some unexplored patients labeled as chronic orchalgia in the literature may have underlying correctable pathology. Surgically correctable pathology such as intermittent testicular torsion, metachronous testicular appendage torsion, and symptomatic hydrocele or varicocele should be excluded in children with chronic orchalgia. Chronic pain specialists should be consulted and associated comorbidities managed. Prior surgical exploration and testicular fixation in children with chronic orchalgia helped reassure patients and families that there was no underlying surgical cause for the pain and facilitated compliance with chronic pain management. Conclusions: Pediatric chronic orchalgia has a multifactorial etiology and is uncommon after scrotal exploration surgery. Comorbidities are common and must be managed. Surgical exploration helps reassure patients that there is no correctable cause for the pain and facilitates engagement with chronic pain management. Table Chronic orchalgia after scrotal exploration in a large cohort: rate and associated comorbidities. Initial scrotal exploration n  = 1084 Undergoing re-exploration n  = 44 Chronic orchalgia n  = 15 (1.4%) Pathology Number (%) Pathology Number (%) Comorbidities noted Appendage torsion 772 (71.2) Appendage torsion 13 (29.6) Anxiety Depression Somatization Joint pain Back pain Chronic pain syndrome Constipation Lower urinary tract dysfunction Varicocele Reactive hydrocele Intermittent testicular torsion Testicular torsion 115 (10.6) Testicular torsion 2 (4.5) Suspected torsion/detorsion 108 (10.0) Suspected torsion/detorsion 17 (38.6) Epididymo-orchitis 52 (4.8) Epididymo-orchitis 4 (9.1) No cause identified 26 (2.4) No cause identified 4 (9.1) Other 11 (1.0) Other 5 (11.4) Complications 61 (5.6) Complications 3 (6.8)